Does colchicine decrease the rate of recurrence of acute idiopathic pericarditis treated with glucocorticoids?. Issue 4 (April 2018) - Mager, Aviv; Talmor, Yeela; Chezar Azzerad, Chava; Iakobishvili, Zaza; Porter, Avital; Kornowski, Ran; Hasdai, David
Highlights: The addition of colchicine has been found to reduce the rate of recurrences of acute pericarditis. We examined colchicine's effects on recurrence of acute pericarditis pretreated with prednisone. In our patients, addition of colchicine to prednisone did not decrease the rate of recurrence. Abstract: Background: The traditional treatment of acute pericarditis includes non-steroidal anti-inflammatory agents (NSAIDs) or glucocorticoids. The addition of colchicine has been found to reduce the rate of recurrences. Glucocorticoids, however, may attenuate this effect, although the available data are limited. We examined the impact of colchicine on the rate of recurrence of acute idiopathic pericarditis pretreated with prednisone. Methods: The frequency of recurrence in patients hospitalized for acute idiopathic pericarditis in a tertiary medical center in 2004–2014 who were treated with glucocorticoids or with non-steroidal therapy was assessed from the computerized hospital database. A retrospective design was used. Results: The cohort included 199 patients aged 18–86 years. Sixty-two (31%) were treated with prednisone, 42 with colchicine and 20 without, and 133 with non-steroidal therapy; in 4 patients, therapy was not detailed. Follow-up ranged from 13 to 147 months (median, 48 months). Fifty-three patients (26.6%) experienced at least one recurrence of pericarditis. The recurrence rate was significantly higher in patients who received prednisone and colchicine (17/42, 40.5%) than in patients who received NSAIDs or aspirin and colchicine (8/44, 18.2%, p = 0.03) or any non-steroidal therapy (30/133, 22.6%, p = 0.03). There was no difference between the rate of recurrence in patients who were treated with prednisone alone (5/20, 25%) and those treated with NSAIDs or aspirin and colchicine or with any non-steroidal therapy ( p = NS). Baseline characteristics and duration of follow-up were similar in patients with and without recurrence. Hospital stay was longer in patients treated with prednisone alone as compared to patients treated with prednisone and colchicine. There were no other differences in baseline characteristics between these groups. Conclusions: The addition of colchicine to prednisone in patients admitted for acute idiopathic pericarditis does not reduce the risk of recurrence. This finding suggests that prednisone blunts the salutary effects of colchicine.